Proactive Vitality Management, Work–Home Enrichment, and Performance: A Two-Wave Cross-Lagged Study on Entrepreneurs - Tisu, Luca; Vîrgă, Delia (Frontiers in Psychology, 2022)
This study provides a cross-lagged examination of the relationships between proactive vitality management, work–home enrichment, and entrepreneurial performance. Specifically, based on the Job Demands-Resources and Conservation of Resources theories, we postulate a mediation model where proactive vitality management leads to entrepreneurs transferring resources developed in their work role to thrive in their home role (i.e., work–home enrichment), resulting in augmented entrepreneurial performance. The hypotheses were tested with data collected at two time points, 1 onth apart—T1 (N = 277) and T2 (N = 249), from Romanian entrepreneurs. We analyzed autoregressive, causal, reversed, and reciprocal models to test the mediation model. In the linkage between predictor and outcome variable, the reversed model is the best-fitting model, showing that proactive vitality management is only a distal precursor of performance. However, the best-fitting models for the relationship between predictor and mediator and between mediator and outcome were the reciprocal models. Thus, proactive vitality management and work–home enrichment have reciprocal effects on each other over time, as was the case between work–home enrichment and entrepreneurial performance. These results are in line with the resource gain cycle perspective of the Conservation of Resources theory. Employing proactive behaviors to optimize functioning at work enables the transfer of resources to the home role. Potentiating one role through aspects of another will thus generate additional resources reflecting on entrepreneurial performance. Hence, this study provides insights into precursors and mechanisms that can shape entrepreneurial performance.